1902–03 Va. Acts & Resolutions 155–57, Extra Session, ch. 148, § 6, pt. 18. - (:unkn) unknown (General Publisher, 1903)
The aggregate value of all shot-guns, rifles, muskets, and other fire-arms, bowie knives, dirks, and all weapons of a similar kind: provided, that all fire-arms issued by the State to members of volunteer companies, or for purposes of police, shall not be listed for taxation (along with other tangible property taxed at twenty cents per 100.00)
--
Keywords: TAX - PROPERTY OR SALES